Analytical Study of Elemental Composition and Heavy Metal analysis in Muthuchippi parpam during Various Stages of Preparation - Balasubramani, Abarna; Ramasamy, Suresh; Marimuthu, Raghavi; Ramamoorthy, Karpagambal (Asian Journal of Biological and Life Sciences, 2025)
Background: Muthuchippi Parpam, a traditional Siddha calcined preparation, is known for its therapeutic properties in strengthening bones and treating musculoskeletal diseases. Objectives: This study employs ICP-OES analysis to understand its elemental composition, ensuring safety and efficacy. Materials and Methods: The use of Siddha formulations in clinical practice holds great promise for addressing non-communicable diseases, with investigations often focusing on reverse pharmacology to understand their therapeutic properties. Results: The results show increased concentrations of essential elements like calcium, zinc, magnesium, and potassium after purification and calcination. Conclusion: The presence of zinc, calcium, and magnesium suggests potential benefits for treating musculoskeletal diseases like osteoporosis and arthritis. This study highlights the importance of scientific validation of traditional Siddha formulations, promoting evidence-based practice and integration into modern medicine.
Keywords: Muthuchippi Parpam; ICP-OES; Purification; Siddha Medicine; Calcium carbonate